Fart quest - Reynolds, Aaron, 1970- (Reynolds, Aaron, 1970- Fart quest (Series), 2020)
After their masters are vaporized in a goblin battle gone badly, Fart, Pan, and Moxie, three lowly apprentices, decide to impersonate their mentors and pick up the mantle as heroes of the realm. But they need more than a fancy robe, magic staff, and book of magical beasts to be real heroes. They need a quest! So when The Great and Powerful Kevin puts out a call for help, seeking the coveted Golden Llama and its magical golden fart, young Fart and his friends jump at the chance and embark on a journey they were destined for.